An Evaluation of National Institutes of Technology (NITs) Library Websites - Kaushik, Anna (DESIDOC Journal of Library & Information Technology, 2015)
Advent of internet technologies specially, website is considered as a most efficient medium to catch and disseminate diverse kind of information, thus, every institution has its own website and is using this medium for imparting variety of information to the targeted users. This study aims to evaluate and analyse the services, facilities and other information available on the library websites of 28 National Institute of Technology (NITs) between February1-28, 2015, by using a checklist. The results of this study revealed that the majority of NIT library websites are providing information with regard to their name, logo, about library book collection, electronic resources, accuracy, diverse services and sections, but, lacking of library mission statements, currency, reliability search interfaces, Web 2.0 applications and cutting edge technologies like cloud-based services. It is also discovered from this study that most of NIT library websites need to improve. This study will be helpful to judge the quality and diverse facilities present on the 28 NIT library websites in India.